Correctional officers and the use of force as an organizational behavior - Schultz, William J. (Criminology, 2023)
During the past 30 years, bureaucratic managerialism has reshaped how prison staff maintain order. Policies and graduated disciplinary models have replaced coercive methods, reducing disciplinary use of force by prison staff against incarcerated people. Managerialism, however, disguises deep problems in the interpretation and enforcement of use-of-force policies. Drawing on 131 semistructured interviews with Canadian correctional officers (COs), I show how managers and prison staff interpret and negotiate policies to justify using force to maintain order. Although COs frame policies and management supervision as significant checks on their actions, they also suggest that inconsistencies in policy interpretation and implementation facilitate certain kinds of use-of-force decisions, which I define as "construction" and "outsourcing." I conclude by discussing the broader organizational implications of these findings.